2021
DOI: 10.1159/000517460
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stress on Health in Childhood and Adolescence in the Era of the COVID-19 Pandemic

Abstract: <b><i>Background:</i></b> The ongoing pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is posing many challenges to global health. Efforts from the whole scientific community have shed light on the pathogenetic mechanisms and the clinical features of SARS-CoV-2 infection as well as on potential therapeutic strategies. <b><i>Summary:</i></b> The consequences of stress related to social isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…A few recent studies ( 43 , 44 , 45 ) investigated the impact of COVID-19 and quarantine on mental health of children and adolescents, reporting a significant increase in behavioral and emotional disorders as a consequence of school closures. Post-traumatic stress disorder has been described in 30% of children during quarantine or social isolation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies ( 43 , 44 , 45 ) investigated the impact of COVID-19 and quarantine on mental health of children and adolescents, reporting a significant increase in behavioral and emotional disorders as a consequence of school closures. Post-traumatic stress disorder has been described in 30% of children during quarantine or social isolation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical studies have elaborated on the consequences of stressful conditions during the COVID‐19 pandemic. As individuals have become more socially isolated and stressed, this exacerbated different mental health problems including depression and anxiety among both adolescents and adults (Cianfarani & Pampanini, 2021 ; Coiro et al., 2021 ; Czeisler et al., 2020 ; Diaz‐Martinez et al., 2021 ; Magson et al., 2021 ). Further, consistent with GST, studies have found an increased use of alcohol and cannabis among young people and adults to cope during the pandemic (Diaz‐Martinez et al., 2021 ; Dumas et al., 2020 ; Grossman et al., 2020 ; MacMillan et al., 2021 ).…”
Section: Explanations Of the Relationship Between The Covid‐19 Pandem...mentioning
confidence: 99%
“…In addition to the potential of immediate mental health impacts, the pandemic may have long-term impacts on adolescents' physical, social, and emotional health due to increased stress during a period when the physiological systems that regulate and respond to stress are still developing ( 6 ). For example, social isolation is a stressor shown to be adversely associated with children's developing stress response systems ( 7 ).…”
Section: Introductionmentioning
confidence: 99%